2020 Kansas State University Industrial Hemp Dual-Purpose and Fiber Trial - Jason Griffin; Kraig Roozeboom; Lucas Haag; Andrew Euler; Michael Shelton; Tami Myers; Matthew Nielsen; Jared Petz; Clint Wilson (Kansas Agricultural Experiment Station Research Reports, 2021)
Hemp is a broad term used to describe the many varieties ofCannabis sativaL. that produce less than 0.3% tetrahydrocannabinol (THC). The crop is globally significant, but only recently was allowed to be grown again in the United States. There are many uses for industrial hemp, which include oil, seed, and fiber, and the market for industrial hemp is rapidly growing as more states are legalizing its production. The market for industrial hemp is expected to grow from 5.33 billion in 2020 to 15.26 billion (15.8%) by 2027 as it gains more popularity (Grand View Research 2021, Valuates Reports 2021). The main components driving the industrial hemp market is the demand for CBD, which provides potential health benefits and hemp fiber. Biofuel from industrial hemp is also expected to stimulate the market and demand for hemp in the future. Varieties have been selected for improved fiber and grain production that have numerous industrial uses. However, the data only exist from a single growing season (2019) regarding adaptability or production of these varieties in Kansas (Griffin et al., 2020). Hemp could be added to diversify a crop rotation and to provide new market opportunities for growers.
Keywords: fiber hemp; dual-purpose hemp; industrial hemp; hemp varieties; hemp trials